Estudio del nivel de satisfacción laboral basado en análisis de parámetros de evaluación, para valorar el grado de compromiso organizacional - Gavilanes López, María Fernanda (2009)
The following degree work was based on the study of the level of job satisfaction based on the analysis of evaluation parameters, to assess the degree of organizational commitment. For the realization of the present study, a standardized survey designed by Dr. Alfonso Dávila was taken by the teachers who provide their academic services in the psychology degree at the University of the Americas in the city of Quito. The purpose of this work is to determine basic aspects of the organizational culture based globally on parameters of job satisfaction existing among the staff of professors of psychology and also specific aspects of their work environment in teaching quality. Try to obtain specific guidelines to improve the level of satisfaction of the teaching staff and evaluate the critical aspects of the evaluation. The results obtained from them will serve to assess the degree of satisfaction.